The Relationship Between Sleep Quality With Fat Mass and BMI Among Students of Medicine Faculty Unjani - Kharissa Rahma Fitrah Deani; Apen Afgani; Dinar Mutiara (Sean Institute, 2026)
Sleep is one of the physiological needs that plays a role in maintaining the body's metabolic balance. Poor sleep quality can affect the regulation of hormones related to appetite, that potentially increase fat mass and Body Mass Index (BMI). Medical students are at risk of experiencing sleep quality disorders due to high academic demands. This study aims to determine the relationship between sleep quality and fat mass and BMI among medical students at the Faculty of Medicine, Jenderal Achmad Yani University, from class of 2022 and 2023. This study used a cross-sectional design. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI), height was measured using a microtoise, weight was measured using a beam balance scale, fat mass was measured using Bioelectrical Impedance Analysis (BIA), and BMI was calculated as weight (kg) divided by height (m)². Data analysis was tested by using Spearman's correlation test. 110 people were taken as the sample. The results of the analysis showed that there was no significant relationship between sleep quality with fat mass (p=0.565) and BMI (p=0.200). This may be influenced by lifestyle factors, such as physical activity and diet, also stress levels, which play a role in determining body composition.